Insights into the Changing Perspectives of Multiple Sclerosis in India. (8th June 2011) - Pandit, Lekha
Abstract : Multiple Sclerosis (MS) is being diagnosed in increasing numbers in metropolitan cities of India for which the availability of specialist neurologists and magnetic resonance imaging (MRI) facilities are primarily responsible. Epidemiological data are unavailable. Existing data have been obtained from small often retrospective studies from different parts of the country. These earlier studies suggested that optic nerve and spinal cord involvement are considerably high, and that perhaps optic spinal MS was the most prevalent form in India. On this basis it was also speculated that neuromyelitis optica (NMO) may be overrepresented in Indians. However in recent times, prospective studies backed by MRI data have shown no distinct differences between MS seen in the west and India. Sero positivity for NMO IgG is low though NMO phenotype disorders constitute nearly 20% of demyelinating disorders in India. Genetic susceptibility for MS among Indians may be similar to that for white populations. In the major histocompatibility complex (MHC), HLA DR1*1501 has been strongly associated with MS in Indians. A recent study that evaluated the established non-MHC multiple sclerosis loci in a small data set of Indian patients suggested a strong similarity with white populations. This review highlights some of the background information available on MS from India and so also some recent studies that unveiled the disease characteristics in Indian patients.